Production model based on lean manufacturing and SLP to increase productivity in an apparel sector MSME - Pavletich Gonzalo, Diego Andres (2023)
In this scientific article, an integrated production model is presented to face the problems faced by a company in the clothing sector, which has low productivity, much lower than the industry standard. For this, in the said model, the use of VSM as a diagnostic tool, the application of lean manufacturing tools (5S & Kanban), and systematic layout planning as a solution to the problems presented by the analyzed pajama manufacturing company. With the application of the proposed integrated model, it is planned to increase the company's competitiveness, increasing its productivity by 23.86% to reach the industry standard. Furthermore, after analyzing and comparing the simulation results in the Arena Simulator software of the current situation and the proposed integrated production model, an increase of 30.61% in the company's productivity was observed. This result is due to increased efficiency and effectiveness, reduced waiting times, and transport waste.